Some Applications of Ordinary Differential Operator to Certain Multivalent Functions - Müfit Şan; Hüseyin Irmak; Ayhan Şerbetçi (Journal of Mathematics)
The aim of this paper is to apply the well-known ordinary differential operator to certain multivalent functions which are analytic in the certain domains of the complex plane and then to determine some criteria concerning analytic and geometric properties of the related complex functions.